Pengaruh Wadah dan Lama Penyimpanan Serbuk Sari terhadap Viabilitas Serbuk Sari Kelapa Sawit (Elaeis guineensis Jacq.) - Mery Hasmeda; Zainal Ridho Djafar; Dwi Asmono; Tardas M.L. Tobing (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
Pollen of oil palm is one of important components that might affect productivity of oil palm (Elaeis guineensis Jacq.). Viability and availability of pollen directly affect the quality and quantity of oil palm. The aim of this research was to evaluate the effect of storage container and time of storage to pollen viability. This research has been conducted at Seed Preparation laboratory of PT. Sampoerna Agro Tbk, PT. Bina Sawit Makmur Mesuji Kabupaten Ogan Komering Ilir. The experimental design being used was Factorial Randomized completely design with two factors were storage containers i.e. Pirex tube reaction (M1), Film Ampoule (M2), Vial bottle (M3) and Glass Ampoule (M4) and time of storage i.e. storage for 0, 1, 2, 3, 4, 5 and 6 months. Each treatment was replicated three times. Parameters being observed included pollen viability, potential of maximum growth and pollen growth rate. The results showed that storage container and time of storage influenced potential maximum growth significantly but there was no effect on pollen viability and pollen growth rate